ANALISIS KEBUTUHAN ANGKUTAN UMUM RUTE SINGKAWANG – SAMBAS - Nurhasanah, Siti; Ariyadi, Teddy (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
This research is aimed to find out the optimal number of fleets at present and to predict for the next 5 years based on population growth then determine the need of current and next 5 years public transportation with reference to passenger number, load factor, vehicle operational cost and income earned from survey and analysis results. Given the optimal number of fleets needed to serve the needs of public transport (small bus) on the route Singkawang - Sambas is expected to improve service levels to be better, meaning there is no shortage or excess number of fleets.The calculation of population growth prediction is North Singkawang now amounts to 24,434 people for 2020 to 27,166 people. Selakau District residents now number 31,751 people for 2020 to 33,530 inhabitants. Residents Kecamatan Pemangkat now amounted to 46,265 people for the year 2020 amounted to 48,013 inhabitants. Residents of Semparuk sub-district now number 25,085 people for 2020 amounted to 26,484 inhabitants. The population of Tebas sub-district now amounts to 66,872 people for 2020 totaling 70,310 inhabitants. The population of Sebawi District now amounts to 16,627 people for the year 2020 totaling 17,728 inhabitants. Residents of Kecamatan Sambas now number 49.127 people for 2020. The average number of passengers surveyed for Singkawang - Sambas route is 669 passengers while Sambas - Singkawang 1099 passengers, and the most crowded passengers on Monday as many as 1917 passengers. Estimated passenger growth for 2020 based on population growth amounted to 2040 passengers. With the current population growth of 260,161 people for the year 2020 to 276,907 inhabitants.From the analysis result based on the load factor in the optimal number of public transportation with Singkawang - Sambas route for now is 33 units from 34 fleets operating now. Based on the number of population growth for the next five years, the optimal number of fleet is 35 units of vehicles. So for the next five years the number of vehicles that operate now is still quite sufficient only need the addition of 1 unit of fleet but the age of the vehicle is too old to operate.